La Prise de Calais, une campagne de conservation-restauration épique ? - Olivier Verheyden (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
A monumental painting measuring 25m2, found in a basement is menaced by total decay. The painting is a replica of a 19th century original and has been executed shortly after. Conservation treatments will be a challenge for a team of students in which promises to be an outstanding educational experience.